Organ Preservation and Late Functional Outcome in Oropharyngeal Carcinoma: Rationale of EORTC 1420, the “Best of” Trial - Stelmes, Jean-Jacques; Gregoire, Vincent; Poorten, Vincent Vander; Golusiñski, Wojciech; Szewczyk, Mateusz; Jones, Terry; Ansarin, Mohssen; Broglie, Martina A.; Giger, Roland; Klussmann, Jens Peter; Evans, Mererid; Bourhis, Jean; et al. (Frontiers in Oncology, 2019)
Dysphagia represents one of the most serious adverse events after curative-intent treatments with a tremendous impact on quality of life in patients with head and neck cancers. Novel surgical and radiation therapy techniques have been developed to better preserve swallowing function, whilst not negatively influencing the local control rates and/or overall survival. This review focuses on the current literature of swallowing outcomes after curative treatment strategies. Available results from recent studies relevant to this topic are presented, demonstrating the potential role of new treatment modalities for early- and intermediate-stage oropharyngeal cancers. Based on this we present the rationale and design of the currently active EORTC 1420 “Best of” trial, and highlight the potential of this study to help prioritizing either surgery- or radiation-based treatment modalities for the treatment of oropharyngeal cancer in the future.